Rejuvenating the Market for Earth-Based Building Construction Materials in a Developing Economy - William Nwaki; Emmanuel Eze (Civil and Sustainable Urban Engineering, 2022)
Earth-based materials are useful in building and engineering construction projects globally, but they have largely remained unextracted and wasted, and their use has been limited to rural areas and avoided in modern buildings in the cities. The sustainability market in developing countries is still largely unsaturated and undertapped. This situation is blamed on lack of knowledge of the potential, benefits, and characteristics of green and sustainable building materials. This study aimed at determining the benefits of earth-based materials that could lead to the rejuvenation of the market for their adoption in building construction projects in the urban areas of a developing economy. The study adopted a structured questionnaire administered via electronic means to construction experts using the snowball sampling technique in Nigeria. With a response rate of 62.94% and a reliability index of over 0.90, the gathered data were analysed using frequency, percentage, and exploratory factor analysis (EFA). The study revealed that the main clusters of benefits of earth-based materials that can stimulate the market for these materials in urban areas are "cost and pollution-related benefits," "emissions and environmental benefits," "waste and workability benefits," "sound and fire-related benefits," and "thermal insulation and resource efficiency." The study recommended that housing investors, clients, and stakeholders should capitalise on the availability of large quantities of earthen materials to improve the quantity of housing provisions in cities and urban areas.